Dry mouth diagnosis and saliva substitutes—A review from a textural perspective. Issue 2 (15th December 2020) - Hu, Jing; Andablo‐Reyes, Efren; Mighell, Alan; Pavitt, Sue; Sarkar, Anwesha
Abstract: The aim of this review is to assess the objective and subjective diagnosis, as well as symptomatic topical treatment of dry mouth conditions with a clear focus on textural perspective. We critically examine both the current practices as well as outline emerging possibilities in dry mouth diagnosis and treatment, including a patent scan for saliva substitutes. For diagnosis, salivary flow rates and patient‐completed questionnaires have proven to be useful tools in clinical practice. To date, objective measurements of changes in mechanical properties of saliva via rheological, adsorption, and tribological measurements and biochemical properties of saliva such as assessing protein, mucins (MUC5B) are seldom incorporated into clinical diagnostics; these robust diagnostic tools have been largely restricted to application in non‐clinical settings. As for symptomatic treatments of dry mouth, four key agents including lubricating, thickening, adhesive, and moisturizing agents have been identified covering the overall landscape of commercial saliva substitutes. Although thickening agents such as modified celluloses, polysaccharide gum, polyethylene glycol, and so forth are most commonly employed saliva substitutes, they offer short‐lived relief from dry mouth and generally do not provide boundary lubrication properties of real human saliva. Innovative technologies such as self‐assembly, emulsion, liposomes, and microgels are emerging as novel saliva substitutes hold promise for alternative approaches for efficient moistening and lubrication of the oral mucosa. Their adoption into clinical practice will depend on their efficacies, duration of relief, and ease of application by the practitioners and patient compliance.